Carbon taxes, poverty and compensation options - Roantree, Barra (The Economic and Social Research Institute, 2020)
This paper examines how the Irish carbon tax can be raised without increasing poverty and disproportionately affecting low-income households. It shows that poverty can in fact be reduced and the lowest-income fifth of households left better-off using a third of revenues from a carbon tax rise on targeted increases in welfare payments, as proposed in the recent Programme for Government. This reverses the regressive impact of an uncompensated carbon tax rise, which arises because goods subject to the carbon tax make up a larger share of spending for lower- than higher-income households.
PUBLISHED
Keywords: Inclusive Society